Influence of polymer binder structure on the properties of the graphite anode for lithium-ion batteries - Osinska-Broniarz, Monika; Martyla, Agnieszka; Majchrzycki, Lukasz; Nowicki, Marek; Sierczynska, Agnieszka (European Journal of Chemistry, 2016)
This paper discusses the impact of the structure and properties of three different polymer binders: polyvinylidene fluoride, sodium carboxymethyl cellulose and polyvinyl alcohol, on the electrochemical properties of spherical graphite anodes for Li-ion batteries. Electrochemical tests indicate that the nature of polyvinylidene fluoride contributes in decreasing the cycle life of graphite electrodes in contrast to effective water-based binders. This study demonstrates the possibility of manufacturing graphite-based electrode for Li-ion batteries that cycle longer and use water in the processing, instead of hazardous organic solvents like N-methylpyrrolidone, thereby improving performance, reducing cost and protecting the environment.